Effects of soil inhomogeneity on seepage behavior within embankments - Koji Nakashima; Katsuyuki Kawai; Hideaki Yoshida (Tạp chí Khoa học và Công nghệ, 2023)
Heavy rain events that accompany recent climate change, have triggered disasters of embankment structures, such as road embankment and levee. Internal erosion, which is the migration of soil particles following seepage flow, causes inhomogeneity of the soil properties of the embankment. However, there are very few studies investigating the effects of soil inhomogeneities on the seepage behavior of groundwater within embankment. In this study, small-scale modelling tests were performed under repeated seepage flow histories. As a result, the groundwater table gradually increased in accordance with the number of seepage repetition. Modelling the fluctuation of permeability due to internal erosion following seepage flow was additionally performed using the soil/water/air coupled finite element analysis, and seepage behavior was investigated. In these analyses, the lower permeability of the toe of embankment was shown to possibly cause an increase in upward water pressure.